The Effect Investıgatıng Levels of Attıtudes of Student’s Studyıng at Secondary Schools Towards Physıcal Educatıon and Sports Class - Yaşar Çoruh; Sedat Okut (Türk Spor ve Egzersiz Dergisi)
In this study, The aim of this study is to research the relationship between the attitude scale of the students studying at secondary schools in Muş province and districts in 2015-2016 education year and sports and other variables. While the population of this study consists of the secondary school students studying in Muş province, the sample of the study constitutes 382 women and 384 men with a total number of 766 participating in the research voluntarily and also studying at secondary schools in Muş province and districts. The frequency and percentage distribution have been used to determine the demographic features in the analysis of datum and Independent Samples T test has been used to examine the relationship between two independent variables and also Anova Variance analysis tests were used to examine the relationship between the variables more than two. The relationship between variables was interpreted by being taken as a basis of p=.,05 significance level. As a result, according to the findings it has been pointed out that thee is a significant difference between the students’ attitude towards Physical Education class and Their Mothers’ Employment  Status, Fathers’ Occupation, Class Levels, the condition whether they do sports in their spare time off school and the condition that they do sports in a club. To ensure for students to participate actively in physical education and sports classes during learning process, various kind of quality and content extended studies aimed at which variables causing to diverge students’ attitudes stem from.